Analysis of Students' Mathematical Communication in Solving AKM Problems by Students with Varying Anxiety Levels - Faizah Nurbani Wisnu Putri; Yus Mochamad Cholily; Zukhrufurrohmah Zukhrufurrohmah (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This qualitative study analyzes students' mathematical communication while solving minimum competency assessment-type questions concerning their levels of math anxiety. The study involved 27 students in class VII B at Junior high school, with six junior high school students as subjects. Data were gathered through math anxiety questionnaires, tests with minimum competency assessment question types, and student presentation assessment sheets. The completed questionnaire was used to select subjects for the tests and presentations. The test sheet contains questions on the AKM type of flat material and three description questions. The data were analyzed through reduction, presentation, and conclusion stages. Findings indicate that students' math anxiety levels were high, medium, and low, with moderate anxiety being the most common. While no students showed low mathematical communication skills, three students were found to have average skills, and three students demonstrated high mathematical communication abilities.